ChemInform Abstract: Organic Stereochemistry. Part 3. Other Stereogenic Elements: Axes of Chirality, Planes of Chirality, Helicity, and (E, Z)‐Diastereoisomerism. Issue 30 (4th July 2013) - Testa, Bernard
Abstract Review: 64 refs.